Hepatocellular carcinoma tumour burden score to stratify prognosis after resection. Issue 7 (14th February 2020) - Tsilimigras, D. I.; Moris, D.; Hyer, J. M.; Bagante, F.; Sahara, K.; Moro, A.; Paredes, A. Z.; Mehta, R.; Ratti, F.; Marques, H. P.; Silva, S.; Soubrane, O.; et al.
Abstract : Background: Although the Barcelona Clinic Liver Cancer (BCLC) staging system has been largely adopted in clinical practice, recent studies have emphasized the need for further refinement and subclassification of this system. Methods: Patients who underwent hepatectomy with curative intent for BCLC‐0, ‐A or ‐B hepatocellular carcinoma (HCC) between 2000 and 2017 were identified using a multi‐institutional database. The tumour burden score (TBS) was calculated, and overall survival (OS) was examined in relation to TBS and BCLC stage. Results: Among 1053 patients, 63 (6·0 per cent) had BCLC‐0, 826 (78·4 per cent) BCLC‐A and 164 (15·6 per cent) had BCLC‐B HCC. OS worsened incrementally with higher TBS (5‐year OS 77·9, 61 and 39 per cent for low, medium and high TBS respectively; P < 0·001). No differences in OS were noted among patients with similar TBS, irrespective of BCLC stage (61·6 versus 58·9 per cent for BCLC‐A/medium TBS versus BCLC‐B/medium TBS, P = 0·930; 45 versus 13 per cent for BCLC‐A/high TBS versus BCLC‐B/high TBS, P = 0·175). Patients with BCLC‐B HCC and a medium TBS had better OS than those with BCLC‐A disease and a high TBS (58·9 versus 45 per cent; P = 0·005). On multivariable analysis, TBS remained associated with OS among patients with BCLC‐A (medium TBS: hazard ratio (HR) 2·07, 95 per cent c.i. 1·42 to 3·02, P < 0·001; high TBS: HR 4·05, 2·40 to 6·82, P < 0·001) and BCLC‐B (high TBS: HR 3·85, 2·03 to 7·30; P < 0·001) HCC. TBS could also stratify prognosis among patients in an external validation cohort (5‐year OS 79, 51·2 and 28 per cent for low, medium and high TBS respectively; P = 0·010). Conclusion: The prognosis of patients with HCC varied according to the BCLC stage but was largely dependent on the TBS. Abstract : The prognosis of patients with hepatocellular carcinoma varied according to the Barcelona Clinic Liver Cancer (BCLC) stage; yet, it was largely dependent on the tumour burden score (TBS). Following resection, patients with similar TBS had comparable long‐term outcomes, regardless of BCLC status, suggesting the need for further subclassification of the current BCLC guidelines and refinement of the proposed treatment algorithm using an assessment of total tumour burden. Added value Abstract : Antecedentes: Aunque el sistema de estadificación del Barcelona Clinic Liver Cancer (BCLC) ha sido adoptado en gran medida en la práctica clínica, estudios recientes han enfatizado la necesidad de un mayor refinamiento y subclasificación del sistema BCLC. Métodos: Los pacientes con carcinoma hepatocelular ( hepatocellular cancer, HCC) BCLC‐0, A y B que se sometieron a una hepatectomía con intención curativa entre 2000 y 2017 fueron identificados utilizando una base de datos multi‐institucional. Se calculó la puntuación de carga tumoral ( tumour burden score, TBS) y se examinó la supervivencia global ( overall survival, OS) en relación con la TBS y los estadios BCLC. Resultados: En la serie de 1.053 pacientes, 63 (6%) tenían HCC BCLC‐0, 826 (78, 4%) HCC BCLC‐A y 164 (15, 6%) HCC BCLC‐B. La OS disminuyó de forma incremental en función de la mayor TBS (OS a 5 años; TBS baja: 77, 9% versus TBS media: 61% versus TBS alta: 39%, P < 0, 001). No se observaron diferencias en la OS entre pacientes con una puntuación TBS similar, independientemente del estadio BCLC (BCLC‐A/TBS media: 61, 6% versus BCLC‐B/TBS media: 58, 9%, P = 0, 93; BCLC‐A/TBS alta: 45, 1% versus BCLC‐B/TBS alta: 12, 8%, P = 0, 175). Los pacientes con BCLC‐B/TBS media tuvieron una mejor OS que los pacientes con BCLC‐A/TBS alta (58, 9% versus 45, 1%, P = 0, 005). En el análisis multivariable, la TBS se mantuvo asociada a la OS en el caso de BCLC‐A (TBS media: cociente de riesgos instantáneos, hazard ratio, HR = 2, 07, i.c. del 95%: 1, 42‐3, 02, P < 0, 001; TBS alta: HR = 4, 05, i.c. del 95%: 2, 40‐6, 82, P < 0, 001) y BCLC‐B pacientes (TBS alta: HR = 3, 85, i.c. del 95%: 2, 03‐7, 30, P < 0, 001). La TBS también pudo estratificar el pronóstico entre pacientes en una cohorte de validación externa (OS a 5 años; TBS baja: 78, 7% versus TBS media: 51, 2% versus TBS alta: 27, 6%, P = 0, 01). Conclusión: El pronóstico de los pacientes con HCC varió según el estadio BCLC, pero dependió en gran medida de la TBS.